Transformation Process Of Religious Believers Among Morocco’s Immigrant Women In Spain - Samper Sierra, Sarai (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Moroccan migration towards Spain is every time more feminine. This fact is due to the growing number of single and divorced women who decide to emigrate on their own in order to find better working conditions. This new type of migration is led by urban women, with studies, who play an important economic rolle within their families, breaking therefore with the traditional restrictions on women’s mobility and their participation in the public space. These restrictions are, in Morocco’s case, integrated in a Muslim culture. The following paper tries to offer an approach to the social and economic changes that are in the origin of this new migration, as well as to the way in which these women reinterpret their sense of being Muslims and their Islamic beliefs after migrating to the Spanish society.
Keywords: moroccan women; islam; autonomous immigration; muslim identity; reinterpretation